(untitled) (Revista Rupturas, 2021)
The memories of Potrero Grande’s peasants expose the repercussions from the national development that took place on the southern side of Costa Rica. The dispossession of the peasant economy of the Potrero Grande’s community and its relationship with the arrival of the state institutions during mid 20th century will be analized. The peasant history and the socio-economic transformations from the developmental era, which had an impact on the Potrero Grande community, will be rebuild through memories and other historical sources.